The effect of geogebra software on achievement and engagement among secondary school students - Hidayat, R.; Kamarazan, N. A.; Nasir, N.; Ayub, A. F. M. (Universiti Putra Malaysia, 2023)
GeoGebra software has been identified as a potential aid in the teaching and learning process. This study aims to examine the impact of GeoGebra software on achievement and enjoyment in the context of the polygon topic. A non-equivalent group pretest-posttest design was utilized, and 60 students were randomly assigned to either the experimental or control group. The data collected was analyzed using descriptive and inferential statistical methods with the assistance of SPSS version 26. The findings revealed that the level of achievement and engagement among Form Two students in the study population was already high regarding the Polygon topic. However, the results demonstrated that students who received instruction utilizing GeoGebra software achieved even higher levels of achievement and engagement than those who experienced traditional teaching methods. As a result, integrating GeoGebra software into the classroom proved to be an effective tool for enhancing student achievement and engagement on the Polygon topic among Form Two students. Finally, we found a significant relationship between the experience of enjoyment and the academic performance of second-year students.